Pengelolaan Sampah Plastik Dalam Skala Kecil: Peran Masyarakat Dalam Mengurangi Dampak Lingkungan - Rahayu, Yuli Sri; Nuraeni, Siti; Kaustara, Nur Ramadhini; Maulana, Nanda Akmal; Nuryadi, Duvi Pratama (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2024)
Most plastic waste is not processed properly and can cause pollution to the surrounding environment. This problem is currently being faced by residents of Gunung Putri Bogor District, low knowledge and lack of contribution from residents in managing organic waste and non-organic waste, leads to the dumping and burning of waste in quite large quantities, which can trigger air pollution and disease, so the aim in This service is to evaluate the effectiveness of various waste management methods, especially in the context of waste sorting, to raise awareness of the importance of managing plastic waste on a small scale, as well as providing a positive impact on environmental conservation efforts. It is hoped that the knowledge generated from this research can be used as an initial reference to increase public awareness in waste management and also encourage active community participation in reducing the impact of environmental pollution produced through a triggering approach, namely encouraging behavior change by providing information and training in the form of waste management workshops. plastic so that residents have the opportunity to handle and manage dry waste (organic and inorganic). The method used in this activity was that the researcher gave a pre-test and post-test before and after the activity. The researcher wanted to measure the level of knowledge and understanding, attitudes, and behavior of the participants in waste management. The results achieved by researchers show a growth in knowledge, attitudes, and behavior of participants in the use of small plastic waste as well as the role of the community. So it can be concluded that this activity is effective in increasing public knowledge about waste and how to manage it.